ANALISIS AKUNTANSI PERSEDIAAN BARANG DAGANG PADA TOKO INDOMARET WOLO KABUPATEN KOLAKA - Handayani, Nur Rahma; Syahrir, Sasmita Nabila; Bustang, Bustang (Komunitas Manajemen Kompetitif, 2025)
This research seeks to ascertain the results of recording as well as valuing trade goods making use of the FIFO approach using a computerized permanent system founded on PSAK (Statement of Financial Accounting Standards) Number 14 concerning Indomaret’s inventory Wolo Kolaka keep. This research uses a descriptive type qualitative approach.Primary and secondary date are used as date sources, and the collection techiques use observation, interviews, and documentation.the study’s findings show that the Indomaret Wolo Kolaka store’s system for keeping track of and valuing its trade goods inventory complies with PSAK Number 14 regarding inventory. Suggestions from this research Indomaret Wolo Kolaka Store can hold an inventory card that is recorded manually and matched with a computer